Invitro antidiabetic activity of palmyra sprout extract - Reichal, C.Prathiba; R.V.Geetha (International Journal of Psychosocial Rehabilitation, 2020)
Borassus flabellifer commonly named as Asian palmyra palm, belongs to the family of Arecaceae. It is used for the manufacture of toddy (alcoholic beverages) or boiled down to give jaggery, molasses vinegar and sugar etc. Many surveys as depicted that the plant has been traditionally used as a stimulant, antidote, anti –inflammatory, wound healing, antihelmintic, analgesic, antipyretic, antidiabetic and so on. Diabetes mellitus is a metabolic disease that is characterized0 by hypo and hyperglycemia. To identify the α-Amylase and α-Glucosidase activity of palmyra sprout extract.The Borassus flabellifer is commercially purchased. It was then used for α-amylase and α-glucosidase activity. Alpha amylase activity is performed by Bhutkar and Bhise, 2012 and alpha glucosidase activity is performed by Abideen S and Vijaya Sankar M,2015.The study highlighted the ability of Borassus flabellifer (Palmyra sprout) extract successfully reducing the effect of diabetes in invitro by α-amylase and α-glucosidase activity. Hence, natural α-amylase and α-glucosidase inhibitors from Borassus flabellifer can be used as an effective therapy for treating postprandial hyperglycemia with minimal or with no side effects.